Design and simulation of an automatic room heater control system. Issue 6 (June 2018) - Zungeru, Adamu Murtala; Mangwala, Mmoloki; Chuma, Joseph; Gaebolae, Baboloki; Basutli, Bokamoso
Abstract: This paper presents the design and simulation of an Automatic Room Heater Control system. This system allows the user to set a desired temperature which is then compared to the room temperature measured by a temperature sensor. With the help of a microcontroller, the system responds by turning ON any of the two (2) loads (Fan or a heater) automatically depending on the temperature difference. The Fan is triggered ON when the room temperature is higher than the set temperature and the heater is triggered ON when the room temperature is lower than the set temperature. The system was designed and simulated using Proteus 8, circuit building software used for building electronics system. Proteus software was used to design and simulate the main circuit, and Micro-C hex file was loaded on the Proteus schematic design. For coding the PIC Microcontroller, Micro-C compiler was used. A 5 V DC power supply was designed in order to provide a biasing voltage to most of the active devices used in the system design circuit. The DC power supply was designed and simulated using Multisim software. The system was simulated and simulation results were in accordance to the design specifications.